Recurrence of keloids after application of epidermal growth factor - Joseph, Aneesh; Kochunarayanan, Ajayakumar; Varghese, Fobin; Sadasivan, Kalesh (International Surgery Journal, 2019)
Background: Exact aetiology for keloid formation is yet unknown. The prime goal of the therapy is to decrease the process of scarring. Many modalities of treatment are available for keloids. With current treatment modalities, recurrence rates approaches 75%. This study was conducted to find out whether application of Epidermal growth factor will reduce recurrence rates of keloids, after surgical excision. Methods: An observational study was conducted by collecting details of 40 patients who underwent surgical excision of keloids followed by epidermal growth factor application over the wounds. The patients have been followed up to 6th months post excision and recurrence rates of keloids as well as overall scar quality were analysed. Results: Out of 45 patients included in the study, 16 (35.6 %) were males and rest females. The median age of the study population was 18.0 (with an IQR 16.0; 26.0). Out of 45 patients, 12 patients had family history of keloids (73%). Out of 45 patients, 8 had keloid tendency which amounts to 82%. Out of 45 patient who underwent treatment, 22 patient developed recurrence which is 48.9% Out of 45 patients included in the study, 16 (35.6 %) were males and rest females. The median age of the study population was 18.0 (with an IQR 16.0; 26.0). Out of 45 patients, 12 patients had family history of keloids (73%). Out of 45 patients, 8 had keloid tendency which amounts to 82%. Out of 45 patient who underwent treatment, 22 patient developed recurrence which is 48.9%. Conclusions: There is a dearth of randomized controlled trials supporting the efficacy of epidermal Growth factor in preventing keloid recurrence. The subjective improvements seen in some cases are encouraging. This study will be a foundation for future studies and will highlight the breadth of knowledge yet to be explored by this therapy.